Health impact and cost-effectiveness analysis of gender-neutral versus female-only 9-valent human papillomavirus vaccination in Taiwan - Hung-Hsueh Chou; Pen-Yuan Chu; Ying-Hui Wu; Casey Feng; Wei Wang; Isaya Sukarom; Andrew Pavelyev (PLoS ONE, 2025)
The prevalence of human papillomavirus (HPV)-related diseases in women has declined in countries introducing HPV vaccinations for girls but remains high among men. The objective of this study was to compare the health impact and cost-effectiveness of two HPV vaccination strategies in the pre-adolescent Taiwanese population: nonavalent (9vHPV) gender-neutral vaccination (GNV), and 9vHPV female-only vaccination (FOV). A previously validated dynamic transmission model was adapted to the Taiwanese setting. The model had a 100-year time horizon and assumed an 85% vaccination coverage rate for girls and a 50% rate for boys, lifelong duration of vaccine protection, herd immunity, and a discount rate of 3% for costs and quality-adjusted life-years (QALYs). Costs of vaccination and HPV-related disease (in 2015−2016 new Taiwan dollars [NTD]), QALYs, and incremental cost-effectiveness ratios (ICERs) were estimated. Compared to 9vHPV FOV, GNV prevented 572 additional cases of cervical cancer (a 1.0% decrease) and 57,691 cases of genital warts (−12.6%) in women. In men, 26 additional cases of penile cancer were avoided (−6.6%), as well as 179,207 cases of genital warts (−26.7%), 4,955 cases of head and neck cancer (−9.0%), and 3,880 cases of recurrent respiratory papillomatosis (−15.8%), by use of the 9vHPV GNV strategy versus FOV. Use of 9vHPV GNV instead of FOV would prevent 229 deaths from cervical cancer in women (a 0.6% decrease) and 3,398 deaths from head and neck cancer in men (−8.3%) over 100 years. The 9vHPV GNV strategy resulted in a savings of NTD 1,574,288,155 (1.9%) in disease management costs compared to the 9vHPV FOV strategy and was predicted to be cost-effective, with an ICER of NTD 606,210/QALY. Compared to a 9vHPV FOV strategy, a 9vHPV GNV strategy for 13-year-old girls and boys would result in incremental public health and economic benefits and would be cost-effective in Taiwan.